2023
DOI: 10.5770/cgj.26.658
|View full text |Cite
|
Sign up to set email alerts
|

Do older people with poor sleep quality have worse cardiac autonomic control?

Abstract: Objective To identify the differences in cardiac autonomic control between older people with good and poor sleep quality. Material and Methods This is a cross-sectional study with 40 older people aged ≥ 60 years, registered at a community health center in Petrolina, Pernambuco, Brazil. The sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI). To assess heart rate variability (HRV), the RR intervals (RRI) were recorded for 10 min with a validated smartphone app and a wireless transmitter P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(65 reference statements)
1
1
0
Order By: Relevance
“…However, in our study, we did not observe this link, which may be attributed to potential confounding variables such as recent psychosocial stressors and lifestyle. A study that investigated HRV among older adults (that had a limited sample size) observed no statistically signi cant differences in cardiac autonomic control between older adults with high and low sleep quality [4]. This nding is also consistent with the primary outcomes regarding HRV in our study.…”
Section: Hrv In Geriatricssupporting
confidence: 91%
See 1 more Smart Citation
“…However, in our study, we did not observe this link, which may be attributed to potential confounding variables such as recent psychosocial stressors and lifestyle. A study that investigated HRV among older adults (that had a limited sample size) observed no statistically signi cant differences in cardiac autonomic control between older adults with high and low sleep quality [4]. This nding is also consistent with the primary outcomes regarding HRV in our study.…”
Section: Hrv In Geriatricssupporting
confidence: 91%
“…Older adults are also predisposed to increased daytime sleepiness. Failure to proactively address sleep disturbances has a spectrum of deleterious health consequences [3,4].…”
Section: Introductionmentioning
confidence: 99%